2022
DOI: 10.1097/icl.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Microbiology, and Genetics of Contact Lens–Related and Non–Contact Lens-Related Infectious Keratitis

Abstract: Infectious keratitis is a rare but severe condition associated with a range of ocular and systemic predisposing conditions, including ocular trauma, prior surgery, surface disease, and contact lens (CL) wear. This review explores the epidemiology of infectious keratitis, specifically the differences in disease incidence and risk factors, causative organism profile and virulence characteristics and host microbiome, genetics, gene expression, proteomics, and metabolomic characteristics in CL-related and non-CL-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 74 publications
0
11
0
2
Order By: Relevance
“…Previous studies have found that staphylococci and Pseudomonas aeruginosa were the most prevalent microorganisms found in post-traumatic IK. 12 As shown in Figure 4, the anti-bacterial spectrum of aminoglycosides and quinolones is almost similar, except that aminoglycosides are often effective against methicillinresistant staphylococci while quinolones are not. 13 Conversely, quinolones are effective against chlamydia while aminoglycosides are not.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have found that staphylococci and Pseudomonas aeruginosa were the most prevalent microorganisms found in post-traumatic IK. 12 As shown in Figure 4, the anti-bacterial spectrum of aminoglycosides and quinolones is almost similar, except that aminoglycosides are often effective against methicillinresistant staphylococci while quinolones are not. 13 Conversely, quinolones are effective against chlamydia while aminoglycosides are not.…”
Section: Discussionmentioning
confidence: 94%
“…Noszenie soczewek kontaktowych jest istotnym czynnikiem, predysponującym do infekcyjnego zapalenia rogówki w krajach rozwiniętych. Stanowi przyczynę aż 45-66% nowo rozpoznawanych przypadków, i jednocześnie aż 20-23 % ciężkich przypadków zapalenia rogówki wymagających hospitalizacji [14,15]. Drobnoustroje izolowane najczęściej od pacjentów używających szkła kontaktowe to Pseudomonas aeruginosa i Acanthamoeba spp.…”
Section: Używanie Soczewek Kontaktowych I Ortokorekcyjnychunclassified
“…Zakażenie częściej rozwija się u osób, które nie ściągają szkieł na czas nocnego odpoczynku, nie myją rąk przed ich założeniem, nie dbają o czystość pojemników do przechowywania soczewek i używają wielofunkcyjnego płynu do ich pielęgnacji, który rzadko wymieniają. Jakikolwiek kontakt oka z wodą wodociągową lub ze zbiornika wodnego skażonego Acanthamoeba grozi rozwojem pierwotniakowego zakażenia rogówki [14]. Soczewki roczne stanowią większe ryzyko infekcji, w porównaniu z miesięcznymi czy dwutygodniowymi [16].…”
Section: Używanie Soczewek Kontaktowych I Ortokorekcyjnychunclassified
“…Even with this great diversity, the OS microbiota remains much less rich in comparison to those of the gut, skin, or oral cavity [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%